No Adverse Effects After Radioiodine Treatment at 3 Weeks of Pregnancy. (December 2016) - Radacic-Aumiler, Matea; Kraljickovic, Iva; Edeljic-Turk, Viktorija; Makar-Ausperger, Ksenija; Likic, Robert; Simic, Iveta
Abstract : Abstract: Radioactive iodine is used for the treatment of hyperthyroidism. Because it accumulates in the fetal thyroid, its administration during pregnancy may cause severe and potentially irreversible hypothyroidism in neonates, with consequent mental retardation, and it is contraindicated during the whole pregnancy. We present a case of a pregnant woman inadvertently treated with 1 mCi (37 MBq) of 131 I in the earliest period of pregnancy and subsequently gave birth to a male infant without signs or symptoms of hypothyroidism or any other damage. This case illustrates that when radioactive iodine administration happens around the third week of gestation pregnancy outcome can be normal.